Gamma-aminobutyric acid (GABA) suppresses hemocyte phagocytosis by binding to GABA receptors and modulating corresponding downstream pathways in blood clam, Tegillarca granosa. Issue 134 (March 2023) - Yu, Yihan; Tian, Dandan; Ri, Sanghyok; Kim, Tongchol; Ju, Kwangjin; Zhang, Jiongming; Teng, Shuangshuang; Zhang, Weixia; Shi, Wei; Liu, Guangxu
Abstract: Although accumulating data demonstrated that gamma-aminobutyric acid (GABA), an inhibitory neurotransmitter, plays an important regulatory role in immunity of vertebrates, its immunomodulatory function and mechanisms of action remain poorly understood in invertebrates such as bivalve mollusks. In this study, the effect of GABA on phagocytic activity of hemocytes was evaluated in a commercial bivalve species, Tegillarca granosa . Furthermore, the potential regulatory mechanism underpinning was investigated by assessing potential downstream targets. Data obtained demonstrated that in vitro GABA incubation significantly constrained the phagocytic activity of hemocytes. In addition, the GABA-induced suppression of phagocytosis was markedly relieved by blocking of GABAA and GABAB receptors using corresponding antagonists. Hemocytes incubated with lipopolysaccharides (LPS) and GABA had significant higher K + -Cl - cotransporter 2 (KCC2) content compared to the control. In addition, GABA treatment led to an elevation in intracellular Cl −, which was shown to be leveled down to normal by blocking the ionotropic GABAA receptor. Treatment with GABAA receptor antagonist also rescued the suppression of GABAA receptor-associated protein ( GABARAP ), KCC, TNF receptor associated factor 6 ( TRAF6 ), inhibitor of nuclear factor kappa-B kinase subunit alpha ( IKKα ), and nuclear factor kappa B subunit 1 ( NFκB ) caused by GABA incubation. Furthermore, incubation of hemocytes with GABA resulted in a decrease in cAMP content, an increase in intracellular Ca 2+, and downregulation of cAMP-dependent protein kinase ( PKA ), calmodulin kinase II ( CAMK2 ), calmodulin ( CaM ), calcineurin ( CaN ), TRAF6, IKKα, and NFκB . All these above-mentioned changes were found to be evidently relieved by blocking the metabotropic G-protein-coupled GABAB receptor. Our results suggest GABA may play an inhibitory role on phagocytosis through binding to both GABAA and GABAB receptors, and subsequently regulating corresponding downstream pathways in bivalve invertebrates. Highlights: GABA incubation significantly constrained hemocyte phagocytosis in blood clam. GABA-induced immunosuppression was relieved by blocking of GABAA and GABAB receptors. Cl − -NFκB could be downstream pathway of the binding of GABA and GABAA receptor. The binding of GABA to GABAB receptor triggered cAMP-NFκB and Ca 2+ -NFκB pathways.